2006
DOI: 10.1063/1.2187486
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of pentacene on filled d-band metal surfaces: Long-range ordering and adsorption energy

Abstract: The growth of pentacene on suitable metallic templates is studied by means of low-energy electron diffraction and ultraviolet photoelectron spectroscopy. Highly ordered pentacene single layers can be prepared by deposition on filled d-band metal templates kept at 370 K. The presence of the steps for the Cu(119) vicinal surface and of the Au troughs for the Au(110)-(1 x 2) surface allows the formation of commensurate long-range ordered structures with (3 x 7) and (3 x 6) periodicities, respectively. A detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 36 publications
7
49
0
Order By: Relevance
“…Still several UPS and ARPES studies have reported on the formation of interacting and hybrid states at the organic/noble-metal interface within the substrate d-band region. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] In these studies intense and sharp photoemission features were found upon the adsorption of large (M-Pc, pentacene) and smaller (anthracene, small thiols, adenine) organic molecules. Ab initio calculations and polarization dependent and angular-resolved measurements were also reported generally highlighting the interface character of the photoemission features.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Still several UPS and ARPES studies have reported on the formation of interacting and hybrid states at the organic/noble-metal interface within the substrate d-band region. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] In these studies intense and sharp photoemission features were found upon the adsorption of large (M-Pc, pentacene) and smaller (anthracene, small thiols, adenine) organic molecules. Ab initio calculations and polarization dependent and angular-resolved measurements were also reported generally highlighting the interface character of the photoemission features.…”
Section: Discussionmentioning
confidence: 90%
“…14,15 Despite this difficulty several studies reported on the formation of hybrid molecule-substrate interface states within the single-crystal substrates d-band BE region. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] The present paper focuses on the substrate contribution in the EDC of the adsorbed system and it highlights the importance of the interface scattering when interpreting the EDC of a thin layer of large, π -conjugated organic molecules on noble-metal single-crystal substrates. As will be shown in the following, the adsorption promotes the measurements of EDCs in photoemission that are reminiscent of the metal three-dimensional (3D)-integrated DOS, i.e., EDCs that mimic polycrystalline metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of this choice of substrate is to obtain an aligned film with pentacene lying flat on the surface and oriented along the Cu͑119͒ steps. [9][10][11][12] Extended regions of the substrate with uniform steps and terraces were obtained after several cycles of ion sputtering ͑Ar + , E = 600 eV͒ and annealing at 740 K, which are followed by slow cooling to room temperature ͑RT͒. The copper surface quality was checked by both STM and low-energy electron diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…The copper surface quality was checked by both STM and low-energy electron diffraction. 9 Pentacene was deposited in situ by evaporating pentacene from a resistively heated quartz crucible at a rate of ϳ0.1 nm/ min in a residual pressure always Ͻ5 ϫ 10 −10 mbar. During the deposition, the substrate was kept either at 370 K to limit the adsorption to a single layer 8 or at RT for a higher coverage.…”
Section: Methodsmentioning
confidence: 99%
“…12 This metallic surface is widely used as a template a) lorenzo.massimi@uniroma1.it b) carlo.mariani@uniroma1.it to follow a bottom-up approach in the formation of highly ordered molecular films, thanks to the twofold missing-row reconstruction along the [001] direction, that can drive the formation of one-dimensional (1D) molecular chains. 13,14 MPc adsorption on Au(110)-(1×2) leads to the formation of ordered chains along the [110] direction, with the MPc molecular plane oriented parallel to the surface. 15,16 The planar orientation, in particular for the first single-layer (SL), is due to an interaction between the metal-phthalocyanine orbitals and the Au electronic levels.…”
Section: Introductionmentioning
confidence: 99%